GEOMETRIC DESIGN OF CROWN WORM GEAR WITH STRAIGHT-LINED BLADE PROFILE - Andrianto, Moeso; Litaay, Christina; Harun, Suryadiwansa; Burhanuddin, Yanuar; Arifin, Achmad (Jurnal Rekayasa Mesin, 2024)
Applications for worm gear drives are common in industry. The crown worm drive is a new kind of inventive worm drive that has just been proposed. Nevertheless, no prior research has been done on the geometric design of crown worm gears with straight-lined blade profiles. On the other hand, designing the cutting tool depends on the geometric design of the workpiece surface modeling. As a result, this study proposed a geometric design for the straight-lined blade shape of the crown worm gear. Numerical examples are used to evaluate the accuracy and applicability of the suggested mathematical model. Furthermore, the modeling of a variable center-distance crown worm gear is completed. It is also feasible to model the crown worm gear using different tool profiles, such as concave and convex profiles.